Aplicabilidade, potenciais e desafios dos Pagamentos por Serviços Ambientais para conservação da água no sul do Brasil - Franciele Lausch dos Santos; Renato Azevedo Matias Silvano (Desenvolvimento e Meio Ambiente, 2016)
Payments for Environmental Services (PES) are part of a global context in which the market economy can no longer ignore nature’s resources and how it is used, having to consider it as one of its components, so that human beings can exercise their activities in a way that is not harmful to the ecosystems. In this sense, it is essential to incentive practices that strengthen conservative attitudes. To consider the actual PES, we have to check a number of factors, such as: transaction costs and opportunity, the effects of permanence, leakage and additionality; which this paper sought to apply by analyzing six PES programs aiming the conservation of water resources in Southern Brazil. The observed patterns were: the difficulty in dealing with transaction costs and opportunity as well as the effect caused by the lack of permanence. However, PES programs encouraged environmental services supply owners to change their behavior, therefore encouraging water conservation. Thus, possible PES programs to be implemented in Banhado Grande’s EPA (Environmental Protection Area) are a way to promote the conservation of wetlands — that provide important ecosystem services, in order to minimize conflict between environment and human activities, such as rice growing.